PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN KARTU TELEPON SELULER THREE ALWAYS ON DI RW 007 PONDOK CABE ILIR – PAMULANG - Sulistiawati, Eka; Argo, Jenji Gunaedi (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
Purchasing decision is a decision as an act of ownership of two or more alternative choices. Many factors can influence the purchasing decisions of consumers to a product, such as brand awareness, perceived quality, brand associations and consumen loyalty. This study was conducted to analyze the effect of brand awareness, percceived quality, brand associations and brand loyalty on purchase decisions of celular card Three Always On. Population in this study were residents in the neighborhood RW 007 Pondok Cabe Ilir – Pamulang using celular card Three Always On. Samples taken 80 respondents. Sampling technique in this study was done by using purposive sampling. Is the primary data type. Methods of data collection using questionnaires. The analysis technique used is multiple regression. Results of analysis using SPSS Version 21.Results showed simultaneously and partially brand awareness, perceived quality, brand associations, and brand loyalty positive and significant impact on purchasing decisions. Therefore, suggested in management company should continue to perform the management, development, and improvement of the various dimensions of brand equity, either by using the media campaign strategy, product innovation, and quality of service. Because today many various kinds of brandmobile phone cards issued by competing companies both domestic or international.